Economic efficiency analysis of substitute natural gas (SNG) production in steam gasification of coal with the utilization of HTR excess heat. (1st November 2016) - Krawczyk, Piotr; Howaniec, Natalia; Smoliński, Adam
Abstract: The concept of coal-nuclear synergy assumes the utilization of excess heat from high temperature nuclear reactors in gasification technologies, which will contribute to increased process efficiency and the reduction of atmospheric CO2 emissions. The purpose of this paper was to analyze the feasibility of substitute natural gas generation in the process of steam gasification of coal with the utilization of high temperature nuclear reactors excess heat by means of the United Nations Industrial Development Organization methodology. The sensitivity analysis of the technology proved that market prices (the volume of income) and capital expenditures (both their volume and the fact that they are spent at the beginning of the investment) have the largest impact on the economic efficiency of the technology examined in this study. The study demonstrated that it is possible to achieve economic efficiency of the system analyzed only in case of a 50% increase in substitute natural gas prices, in relation to current market prices, to the level of approximately 0.50 Euro/m 3 . Highlights: Coal-nuclear synergy concept: utilization of excess heat from HTRs in gasification. Increased process efficiency and the reduction of atmospheric CO2 emissions. The feasibility of SNG generation in steam gasification of coal with HTR excess heat. Market prices and capital expenditures most affecting the process eco-efficiency. Economic efficiency of the system achievable with SNG prices of 0.50 Euro/m 3 .